PENGARUH LINGKUNGAN EKSTERNAL DAN LINGKUNGAN INTERNAL TERHADAP STRATEGI BERSAING DAN STRATEGI KEMITRAAN SERTA DAMPAKNYA PADA KEUNGGULAN BERSAING DAN IMPLIKASINYA PADA KINERJA INDUSTRI KECIL DAN MENENGAH DI SUMATRA BARAT - Mirza Mirza (Indonesian Journal of Economics and Business, 2011)
The performance of small and medium industry can be highly achieved  if SMEs have competitive advantage. SMEs have to implement competitive strategy and partnership strategy optimally. Entrepreneurs of SMEs need to understand  the nature of external environment. A study of general  trends and the dynamics of competition  within industry can highlight opportunities that match the capabilities of entrepreneur. It is then important to evaluate the internal capabilities  of enterprise so that these can be mathed with market needs and other external opportunities. In other words, analysis of external environment helps the entrepreneur to determine what business potensial exist, whereas internal analysis reveals what the venture is able to do. The objective of research are to analyze the effect external and internal environment on the competitive strategy and the partnership strategy and its  impact on the competitive advantage and its implication on the performance of small and medium industry in west sumatra.The research methodology used in this study is descriptive and explanatory survey. Total respondents are 140 entrepreneurs of SMEs in West Sumatra. The sample technique uses proporsional cluster random sampling, while data analysis technique used is PLS. The research shows that (1) external and internal environments have significantly effect to competitive strategy simultaneusly, But the influence of internal environments on competitive strategy is higher than the influence of external environments on competitive strategy (2) external and internal environments have significantly effect to partnership strategy simultaneusly, But the influence of internal environments on partnership strategy is higher than the influence of external environments on partnership strategy (3) external and internal environment as well as competitive strategy, and partnership strategy have significantly effect to competitive advantage simultaneusly (4) external and internal environment as well as competitive strategy, partnership strategy and competitive advantage have significantly effect to performance of small and Medium industry simultaneusly.